An investigation of extremity injuries in school-aged children presenting to the emergency department - Ekmekyapar, Muhammed; Sahin, Levent (Annals of Medical Research, 2021)
Aim: It was aimed that various preventive measures should be taken with the demographic characteristics, trauma etiology, injury sites and radiological imaging results of school-age pediatric patients admitted to the emergency department after isolated extremity trauma.Material and Methods: In our two-center study, 748 patients with isolated limb injuries aged 6-17 years were prospectively evaluated. Their gender, age, causes of trauma, requested radiological imaging in patients classified according to injury sites, treatments, requested consultations, hospitalization and discharge rates were examined.Results: The mean age was 12.2 ± 3.2 years. The most common cause of injury (52.8%) was fall while playing. Fall while playing (FWP) and extremity injuries occurring during sport were more in males than females (p = 0.020). When injury sites were compared according to trauma etiologies, injuries were observed mostly in the left upper extremity in FWPs and mostly in the right upper extremity in school accidents (p = 0.009). An orthopedic consultation request was high in patients who underwent splinting and surgical treatment (p = 0.000). While fracture was detected in 136 (18.1%) patients included in the study, splint or Velpeau bandage treatments were applied to 314 (41.9%) patients. Conclusion: In school-aged child injuries, the most common cause was observed to be "fall," which is a preventable cause. Protective measures that will be taken for the safety of children at home, playgrounds, and schools can reduce these injuries.
Keywords: Children; extremity; fall; injuries; trauma